2014
DOI: 10.4103/2230-8598.137715
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of hospital management information systems in Tamil Nadu, India

Abstract: Introduction: Huge investments have been made in implementing computerized Hospital Management Information Systems (HMIS) across the world, including developing countries. Economic evaluation studies have shown that HMIS implementations are benefi cial. While measuring effectiveness, studies have compared the quality of data generated in the HMIS with paper-based systems and have shown that HMIS is more advantageous. However, not all HMIS implementations are successful. Many successful implementations are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…The results show that the accuracy of the information systems has not been in line with expectations.The application was not accurate yet in terms of efficiency, effectiveness, and cost control benefits, so it cannot be used in the decision making process. The disadvatages of system usually because of loss or damage while records and delays in accessing information (18) .…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the accuracy of the information systems has not been in line with expectations.The application was not accurate yet in terms of efficiency, effectiveness, and cost control benefits, so it cannot be used in the decision making process. The disadvatages of system usually because of loss or damage while records and delays in accessing information (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Medical error and adverse drug reaction caused by illegible prescription when using conventional prescription could also be reduced [5]. In Malaysia, Physician and other medical personnel confirmed that much more information they can get in one place compared to conventional paper-based method [10].…”
Section: ) Strengths Of Hmis Implementation In Developing Countriesmentioning
confidence: 99%
“…Most of the studies showed HMIS can improve the effectiveness and efficiency of services. Technically by providing better data, timely available, human error reduction, and can cut user work time compared to paper-based system [1]- [3]- [5]- [9]. The ability of HMIS to provide faster documentation retrieval and high data accuracy enable hospital officer to reduce patients waiting times, manage resources better, and enhanced accountability in hospital [3].…”
Section: ) Strengths Of Hmis Implementation In Developing Countriesmentioning
confidence: 99%
See 2 more Smart Citations